Genome-Wide DNA Methylation Analysis Reveals a Conserved Epigenetic Response to Seasonal Environmental Variation in the Staghorn Coral Acropora cervicornis - Rodríguez-Casariego, Javier A.; Mercado-Molina, Alex E.; Garcia-Souto, Daniel; Ortiz-Rivera, Ivanna M.; Lopes, Christian; Baums, Iliana B.; Sabat, Alberto M.; Eirin-Lopez, Jose M. (Frontiers in Marine Science, 2020)
Epigenetic modifications such as DNA methylation have been shown to participate in plastic responses to environmental change in a wide range of organisms, including scleractinian corals. Unfortunately, the current understanding of the links between environmental signals, epigenetic modifications, and the subsequent consequences for acclimatory phenotypic changes remain obscure. Such a knowledge gap extends also to the dynamic nature of epigenetic changes, hampering our ability to ascertain the magnitude and extent of these responses under natural conditions. The present work aims to shed light on these subjects by examining temporal changes in genome-wide patterns of DNA methylation in the staghorn coral Acropora cervicornis in the island of Culebra, PR. During a 17-month period, a total of 162 polymorphic loci were identified using Methylation-Sensitive Amplified Polymorphism (MSAP). Among them, 83 of these fragments displayed changes in DNA methylation changes that were significantly correlated to seasonal variation as determined mostly by changes in sea water temperature. Remarkably, the observed time-dependent change in DNA methylation patterns is consistent across coral genets, coral source sites and site-specific conditions studied. Overall, these results are consistent with a conserved epigenetic response to seasonal environmental variation. These findings highlight the importance of including seasonal variability into experimental designs investigating the role of epigenetic mechanisms such as DNA methylation in responses to stress.